The Impacts of Systemic Immune-Inflammation Index on Clinical Outcomes in Gallbladder Carcinoma - Sun, Lejia; Jin, Yukai; Hu, Wenmo; Zhang, Mengyuan; Jin, Bao; Xu, Haifeng; Du, Shunda; Xu, Yiyao; Zhao, Haitao; Lu, Xin; Sang, Xinting; Zhong, Shouxian; et al. (Frontiers in Oncology, 2020)
Systemic immune-inflammation index (SII) is considered to be a prognostic marker in several cancers. However, the prognostic value of baseline pre-operative SII in gallbladder carcinoma (GBC) has not been evaluated. This study aimed to determine the prognostic significance of SII and generate a predictive nomogram. We retrospectively studied 142 GBC patients who underwent surgical resection at the Peking Union Medical College Hospital between 2003 and 2017. SII, neutrophil-to-lymphocyte ratio (NLR) and lymphocyte-to-monocyte ratio (LMR) were evaluated for their prognostic values. A multivariate Cox proportional hazards model was used to construct a nomogram. Calibration curves were used to estimate the performance of the nomogram and decision curve analysis was performed to evaluate its net benefit. The predictive accuracy of SII (Harrell’s concordance index [C-index]: 0.624), NLR (C-index: 0.626) and LMR (C-index: 0.622) was evaluated. The multivariate Cox model showed that SII was a superior independent predictor than NLR and LMR were. SII level (≥600) (hazard ratio [HR]: 1.555; 95% confidence interval [CI]: 1.007–2.401; P=0.047), CA19-9 level (≥37 U/ml) (HR: 2.375; 95% CI: 1.487–3.792; P<0.001) and TNM stage (P=0.026) were selected to construct a nomogram for predicting overall survival (OS). The predictive ability of this model was assessed by C-index (0.752). Good performance was demonstrated by the calibration plot. A high net benefit was proven by DCA. SII is an independent prognostic indicator in GBC patients after surgical resection, and the nomogram based on it is a useful tool for predicting OS.